Williams syndrome across languages - Bartke, Susanne; Siegmüller, Julia (Language acquisition & language disorders ;, 2004)
Williams Syndrome (WS), aka Williams Beuren Syndrome, is a developmental disorder that we have known about for some forty years. The cause for WS was detected only recently: a micro deletion on chromosome 7, more specifically at the region of chromosome 7q11.23. The cognitive and behavioral profile in WS is characterized by a marked discrepancy between verbal and non-verbal skills combined with relatively spared linguistic skills. Recent research has shown considerable progress defining the areas of intactness in linguistic abilities. This volume builds on that research, giving an overview of.